Warlord : [an Alex Hawke novel] - Bell, Ted (New York : HarperCollins Publishers, 2011)
Someone from the past has the British crown in his sights again, and has proven once before that these threats are not to be taken lightly. This is just the call to duty British-American M16 counterterrorism operative Alex Hawke needs to get back in action -- if the madman doesn't wreak total havoc first.
Maps on lining papers.
Keywords: Hawke, Alex (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Royal houses -- United Kingdom -- Fiction; Attempted assassination -- Fiction